REACT Strategy: An Innovative Approach to Improving Students’ Chemistry Learning Outcomes - Hasibuan, Desy Rahmayanti; Daulay, Rabiah Afifah (LAVOISIER: Chemistry Education Journal, 2025)
This research aims to determine the application of the REACT strategy as an innovative approach in improving student chemistry learning outcomes. This research was carried out at MAN 2 Padang Lawas in the Even semester of FY 2023/2024. The population in this study were all students in class X MIA with an average number of students per class of 30 people. The sample consisted of 2 classes taken with determination because the number of class X MIA was only 2 classes. The experimental class applies the REACT strategy as an innovative approach, and the control class applies conventional learning. The data collected is processed from the Posttest results. The data were analysed using the independent t-test formula to test the research hypothesis and obtained tcount  ttable (4.67 1.67), so it can be concluded that the application of the REACT strategy as an innovative approach can improve student chemistry learning outcomes. Meanwhile, the gain test for the increase in learning outcomes for the experimental class was 72.60% in the high category, and the control class was 58.50% in the medium category. It can be concluded that the application of the REACT strategy as an innovative approach can improve students' chemistry learning outcomes.